Ameloblastic fibroma - C H Lalitha; Stuti Goyal; Lakshmikanth Perka; Srikant Kodangal (Wolters Kluwer Medknow Publications, 2016)
Ameloblastic fibroma, is a mixed odontogenic tumor, which commonly affects young children under the age of 20 years, with the mandibular premolar-molar region being the most common site of manifestation. This is a case report of a 25-year-old female with a swelling in the right posterior mandibular region since 4 months, which was subsequently diagnosed as ameloblastic fibroma.